OPTIMISASI PENDISTRIBUSIAN PRODUK KRIPIK DALAM KEMASAN DENGAN METODE TRANSPORTASI PADA UD. KERIPIK RUMAH ADAT MINANG - Ir Zulkarnain, Ayu Najmita Binti; Syafitri Lubis, Riri; Cipta, Hendra (JURNAL MathEdu (Mathematic Education Journal), 2024)
Keripik Rumah Adat Minang is a company of snack food where producing packaged sweet potato chips under the brand of rumah adat minang. The distribution of chips is hampered because the number of consumer request in various cities is higher than the amount of capacity in the warehouse, resulting in the distribution process often delays and having to be done repeatedly so that make the distribution costs become large. Plus now, many roads have been closed so that the distribution routes that are traversed are getting farther away, so its certain that the company incurs huge costs for the distribution of chips. The purpose of this research is to apply the north west corner method as an initial solution for allocating how many chips are produced, to apply the stepping stone method as the final solution in minimizing the cost of distributing chips and to help companies minimize the cost of distributing chips. Both methods can solve problems in the distribution of chips from both warehouses to various destination cities. The results showed that the cost optimization obtained by using the north west corner method was Rp. 146,556,705 which succeeded in reducing as much as Rp. 30,579,886 from the initial cost of transportation of Rp 171,555,522 but it was not optimal, so 4 more iterations were carried out using the advanced method, namely the stepping stone method. Thus the cost of transportation distribution is optimal by generating a cost value of Rp. 146,075,000.